1983
DOI: 10.1073/pnas.80.20.6244
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore structure of the physiologically active form (P fr ) of phytochrome

Abstract: Chromopeptides were prepared by proteolytic digestion of phytochrome (far-red absorbing form, Pfr) and of phycocyanin. The phycocyanobilin peptide, the chromophore of which is Z,Z,Z-configurated, was modified to the Z,ZE isomeric chromophore. It has been demonstrated earlier that the Pfr chromopeptide and the Z,Z,E-configurated phycocyanin chromopeptide behave similarly with regard to spectral and chromatographic properties and reactivity. We present evidence here, obtained by high-resolution 'H NMR spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
162
2
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 22 publications
5
162
2
2
Order By: Relevance
“…It is commonly accepted that the first step in the photoconversion from Pr to Pfr is a Z to E isomerization around the C15=C16 double bond between the C-and D-rings of the bilin chromophores. 28 This photoisomerization generally converts the physiologically inactive red light-absorbing Pr form into the active far-red light-absorbing Pfr form and vice versa. The interchange between the Pr and Pfr forms is essential for light-absorbing biological processes in the phytochrome chromophore function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly accepted that the first step in the photoconversion from Pr to Pfr is a Z to E isomerization around the C15=C16 double bond between the C-and D-rings of the bilin chromophores. 28 This photoisomerization generally converts the physiologically inactive red light-absorbing Pr form into the active far-red light-absorbing Pfr form and vice versa. The interchange between the Pr and Pfr forms is essential for light-absorbing biological processes in the phytochrome chromophore function.…”
Section: Introductionmentioning
confidence: 99%
“…147 Recently, this result was confirmed by X-ray crystallography of a truncated phytochrome from Deinococcus radiodurans consisting of the N-terminal 321 amino acids. For plant phytochromes, it has been shown that the first step of the Pr to Pfr photoconversion is a Z to E isomerization of the chromophore around the C15=C16 double bond, 28 which occurs on the picosecond time scale. [149][150][151] Isomerization is followed by spectral changes in the microsecond and millisecond time scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoactivation is thought to be initiated by a double bond isomerization of the chromophore (10,11). Early NMR spectroscopic studies on proteolytic phytochrome fragments (12,13) indicated that this isomerization occurs at the C15═C16 double bond (for numbering, see Fig. 1A), a geometrical change in line with vibrational spectroscopic investigations (14)(15)(16) and results from recent 13 C solid-state NMR (17,18) in which the most significant changes during the light-triggered conversions are confined to rings C and D. Exact geometries of the chromophore in the Pr state have been resolved as periplanar ZZZssa configurations in bacteriophytochromes from Deinococcus radiodurans (19) and Rhodopseudomonas palustris (20) as well as in the more plant-phytochrome-like Cph1 from the cyanobacterium Synechocystis 6803 (21).…”
mentioning
confidence: 99%
“…11). When the chromophore of phytochrome absorbs the appropriate wavelength of light, a conformational change is induced in both the chromophore and the phytochrome, following a Z to E isomerization at the C15-C16 double bond of the chromophore (12).…”
mentioning
confidence: 99%